Impacts on environmental law and regulations on agricultural land-use change and urban pressure: the Algarve case - Eric De Noronha Vaz; Antonio Brito; Peter Nijkamp; Marco Painho (European Regional Science Association (ERSA), 2010)
Land-use change has been an increasing concern in most of Europe. While stakeholder's strategies of coping with land-use change have been constrained mainly due to socio-economic pressures, the natural landscape and fragile ecosystems are neglected by heavy construction and urbanization. However, over the last thirty years regulations have become more explicit regarding environmental impacts at regional level. Spatial assessment of ongoing policies of rural and urban have led in the case of Portugal to some reservations on the consequences of sustainable development and juridical commitment. A good example of this is the agricultural land loss that Portugal has witnessed over the last thirty years, in large part resulting from socio-economic pressures with which policymakers have not been able to cope. The Reserva Agrícola Nacional (RAN transl. National Agricultural Reserve) may be identified as an instrument of planning purposes that identifies and protects the areas prone to agricultural activities due to their morphological, climatic and social context. The RAN has changed its legal status over four times in the last twenty years. These changes have in large been influenced by the policies of sustainable development for the region. However, the ability to defend the interests of agricultural and rural commitments in fragile ecosystems has been largely compromised due to socio-economic interactions brought by pressures of economic growth. Dynamic and statistical modeling approaches may allow a sharper understanding of the consequences of preemption of agricultural land in the Algarve. The spatial properties of data inventories from the RAN and land-covers, allow to assess the changes within the policy context of the Algarve. By approaching a spatial analysis of preemption of agricultural land with overlay of population and urban data, a focus o the consequences of the certain regulations with the dynamics of land-use change become possible. While this paper expands further on the actual existing decrees which offer support to sustainable development in the region, a qualitative assessment of future roles of ethical values and economic efficiency, while offering a constructive position for policy makers regarding the trends of urban / agricultural dichotomy are analyzed.
Keywords: 330